2019
DOI: 10.1186/s12199-019-0782-z
|View full text |Cite
|
Sign up to set email alerts
|

Fermented foods and preterm birth risk from a prospective large cohort study: the Japan Environment and Children’s study

Abstract: Background The dietary pattern of pregnant women is known to be associated with preterm birth (PTB). We investigated whether PTB was associated with intake of fermented food by using data from the Japan Environment and Children’s Study. Methods From a data set of 103,099 pregnancies, 77,667 cases at low risk for PTB were analyzed. The primary outcome measurements were based on PTB. Fermented food (miso soup, yogurt, cheese, and fermented soybeans) consumption was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…To clarify the causal relationship between iron deficiency, Cd absorption, and placenta previa, it is necessary to measure Cd, iron, and ferritin concentrations in the blood throughout pregnancy, especially during the first trimester, which is an important time for normal implantation and placentation [3]. Dietary habits and nutritional status during pregnancy may be related to pregnancy abnormalities [49, 50]; therefore, it is also important to monitor the diet during pregnancy. Furthermore, the JECS study was a cohort study; therefore, it is important to link the relationship between maternal metal exposure, pregnancy abnormalities, and children’s health in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the causal relationship between iron deficiency, Cd absorption, and placenta previa, it is necessary to measure Cd, iron, and ferritin concentrations in the blood throughout pregnancy, especially during the first trimester, which is an important time for normal implantation and placentation [3]. Dietary habits and nutritional status during pregnancy may be related to pregnancy abnormalities [49, 50]; therefore, it is also important to monitor the diet during pregnancy. Furthermore, the JECS study was a cohort study; therefore, it is important to link the relationship between maternal metal exposure, pregnancy abnormalities, and children’s health in the future.…”
Section: Discussionmentioning
confidence: 99%
“…protein has also been reported to inhibit blood pressure [35] and exhibit antioxidant activity [36], whereas soybean isoflavones exhibit anti-cancer effects [37,38] and promote bone formation [39]. Furthermore, intake of miso soup before pregnancy significantly reduces the risk of early preterm birth [40]. In this study, we showed that miso augmented both immunity and immune tolerance under steady-state conditions as activated B cells and Treg cells were increased upon ingestion of miso.…”
Section: Plos Onementioning
confidence: 61%
“…1 on the immune system were shown over generations. As a transgenerational effect of miso, its consumption is inversely associated with the risk of early preterm birth [ 9 ], which is associated with autism and lifestyle-related diseases, such as metabolic syndrome, in humans [ 16 , 17 ]. Furthermore, early preterm birth is associated with inflammation in animal models and humans [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, animal studies have shown that miso has protective effects against stroke [ 5 ], visceral fat accumulation when combined with exercise [ 6 ], and elevation in blood pressure [ 7 , 8 ]. The consumption of miso has also been found to reduce the risk of early preterm birth [ 9 ]. Thus, miso has been proposed to have different health benefits.…”
Section: Introductionmentioning
confidence: 99%